The Soviet Legacy in Russian Foreign Policy - KRAMER, MARK (Political science quarterly, 2019)
After the Soviet Union broke apart in late December 1991 and the Russian Federation emerged as an independent country, Russian political leaders had to confront a wide range of foreign policy issues leftover from the Soviet regime. The series of agreements codifying the dis-solution of the Soviet Union, which led to the formation of the Commonwealth of Independent States (CIS) and broad international recognition of 15 new states by the end of 1991, designated Russia as the “legal successor state” to the USSR, a status that, for many Russian leaders (both then and now), has blurred Soviet and Russian interests. As the oﬃcial successor state, Russia was given sole possession of the vast Soviet nuclear arsenal and was awarded the USSR’s permanent seat on the United...